The angel makers: the true story of the most astonishing murder ring in history - McCracken, Patti (Mudlark, 2023)
Nagyrev, Hungary, 1929. Over 160 mysterious deaths. A group of local wives conspiring together, and one woman at the centre of it all... In 1929, a dark secret at the heart of a Hungarian farming village was finally exposed. For more than 15 years, Nagyrev had harboured a group of serial killers, one of the largest murder rings ever recorded. They came to be known as The Angel Makers. Led by a sharp-minded midwife known as Auntie Suzy, the local wives brazenly rid themselves of unwanted relatives, spooning doses of arsenic into soup and wine, stirring it into coffee and brandy. Murder was just another chore. Over 160 mysterious deaths later, the unlikely gang of murderesses came to justice in a sensational trial reported the world over. With absorbing detail, Patti McCracken pieces together the lives of Auntie Suzy, her wide network of killers, the unsuspecting victims and the villagers who witnessed it all. The Angel Makers is the utterly gripping account of an almost unbelievable - yet entirely true - moment in crime history